Konstruksi/Karakter Hukum Penyalahgunaan Wewenang dan Menyalahgunakan Kewenangan Dalam Tindak Pidana Korupsi - Darmawan, Dicky; Pattiasina, Lidia Priscilla (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: The legal issues in this paper are how the legal construction/character of abuse of authority in corruption crimes and how the basis for the enforcement of offenses/norms of abuse of authority in corruption Purposes of the Research: This writing aims to find out and analyze the legal construction/character of the abuse of authority in corruption Methods of the Research: The research method used is normative, that is, research that primarily examines positive legal provisions and legal principles, explain and predicts in the direcrion of future legal developments. Results/Originality of the Research: The results show that or The findings of this study prove that abuse of authority and abuse of authority is the core of the concept of administrative law relating to the source or birth of authority. This has consequences for the concept of legal responsibility that was born from deviations from the principle of objectives that have been given to the authority.